Customized smart andon system to improve the efficiency of Iidustrial departments - López-Leyva, Josué Aarón; Pérez, M. J. (My University, 2020)
A customized industrial system to realize the supporting requests in manufacturing lines with detailed statistical information is presented. Also called customized smart Andon system. The system is based on a software and hardware design customized for particular industry needs according to the internal organizational structure. The results of the projection are that Andon system permits an important reduction of the time required for attending and finishing whatever problem in the manufacturing line.
Journal of Scientific & Industrial Research
Keywords: Manufacturing lines; Smart Andon system; Campus Ensenada